Continued Failure of Rabies Elimination—Consideration of Challenges in Applying the One Health Approach - Ghai, Siriporn; Hemachudha, Thiravat (Frontiers in Veterinary Science, 2022)
Despite being a preventable disease, rabies continues to kill tens of thousands of humans every year. To achieve the WHO and OIE’s “Zero human deaths from dog-mediated rabies by 2030” goal, the One Health approach is paramount. Unaddressed root cause of rabies transmission for each country is bound by country-specific cultural and social norms, standard operating procedures, and political approaches, thus a country-specific review can help offer up unique sustainable national strategies. This paper intends to highlight the challenges that countries need to address in relation to this goal, by identifying five prevailing barriers to attaining One Health: lack of collaboration, data sharing, proof of burden, policy and legislative support, and the COVID-19 pandemic. By ensuring that temporary disease burden reduction is not misconstrued as progress, that rabies elimination strategies are supported by legislation and account for the restrictions imposed by the COVID-19 pandemic, we will be able to work towards zero human rabies deaths by 2030.